Oligosaccharyltransferase inhibition reduces receptor tyrosine kinase activation and enhances glioma radiosensitivity - Barontini, Marta Beatriz (2019)
Purpose: Parallel signaling reduces the effects of receptor tyrosine kinase (RTK)–targeted therapies in glioma. We hypothesized that inhibition of protein N-linked glycosylation, an endoplasmic reticulum co- and posttranslational modification crucial for RTK maturation and activation, could provide a new therapeutic approach for glioma radiosensitization. Experimental Design: We investigated the effects of a small-molecule inhibitor of the oligosaccharyltransferase (NGI-1) on EGFR family receptors, MET, PDGFR, and FGFR1. The influence of glycosylation state on tumor cell radiosensitivity, chemotherapy-induced cell toxicity, DNA damage, and cell-cycle arrest were determined and correlated with glioma cell receptor expression profiles. The effects of NGI-1 on xenograft tumor growth were tested using a nanoparticle formulation validated by in vivo molecular imaging. A mechanistic role for RTK signaling was evaluated through the expression of a glycosylation-independent CD8-EGFR chimera. Results: NGI-1 reduced glycosylation, protein levels, and activation of most RTKs. NGI-1 also enhanced the radiosensitivity and cytotoxic effects of chemotherapy in those glioma cells with elevated ErbB family activation, but not in cells without high levels of RTK activation. NGI-1 radiosensitization was associated with increases in both DNA damage and G 1 cell-cycle arrest. Combined treatment of glioma xenografts with fractionated radiotherapy and NGI-1 significantly reduced tumor growth compared with controls. Expression of the CD8-EGFR eliminated the effects of NGI-1 on G 1 arrest, DNA damage, and cellular radiosensitivity, identifying RTK inhibition as the principal mechanism for the NGI-1 effect. Conclusions: This study suggests that oligosaccharyltransferase inhibition with NGI-1 is a novel approach to radio-sensitize malignant gliomas with enhanced RTK signaling.